The Kajian Nilai Pendidikan Karakter dalam Kakawin Ramayana Sargah 4 - Ni Luh Putu Juliastini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The values of character education are very important to be instilled in the current era of globalization. The number of cases due to the lack of planting character education in Indonesia still occurs a lot. For example, many cases were carried out by students such as student rules, many students had abortions, sex outside of marriage, marriage occurred at school, and the decline in student character can be seen from the cases of many students who skipped classes, unhealthy dating at school, smoking in the area as if, many students also violate school rules, as well as lack of manners when students meet teachers. The occurrence of cases like that illustrates that character education has experienced a very drastic decline in the world of education, so it is necessary to instill character education more deeply for students. There are many media that can be used to instill character education in students, one of which is through literary works that are widely spread in society. One of the most popular literary works of society today is because of its value content, namely Kakawin Ramayana. Kakawin Ramayana is a literary work that has a lot of character education values contained in its very broad story that can be used as a guide for people's lives.